Getting Progress Right: Measuring Progress Towards the MDGs Against Historical Trends - Stephan Klasen; Simon Lange (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
Most numerical targets within the framework of the Millennium Development Goals (MDGs) are overly ambitious for the poorest countries when interpreted as country-specic goals. As a consequence, the current system undermines accountability and ownership and jeopardizes the public support the MDGs have drawn in the past. This paper proposes an alternative approach to evaluating progress towards non-income MDGs that allows a sensible appraisal of countries' performance.
Keywords: I15; I18; I25; I28; I32; 330